Adams and Jefferson : a revolutionary dialogue - Peterson, Merrill D. (Lamar memorial lectures ;, 2021)
Draws a parallel between the backgrounds, experiences, personalities, and intellectual styles of John Adams and Thomas Jefferson, and examines their work in the achievement of independence and the design of new governments for Massachusetts and Virginia. Proceeds to examine their contrasting responses to the Old World, focusing on their relationship to the coming of the French Revolution and carrying the theme forward into the establishment of the new American government under the Constitution. Also examines the "Revolution of 1800" beginning with the contest between Adams and Jefferson for the presidency in 1796, and finally, the reconciliation of the two men, examining at some length their famous correspondence, with a special view to their contrasting assessments of the age of revolution through which they had lived and to their hopes for the future.